PENGARUH NET PROFIT MARGIN DAN TOTAL ASSETS TURNOVER TERHADAP PERTUMBUHAN LABA (SUBSEKTOR INDUSTRI SEMEN),TBK PERIODE TAHUN 2017 - 2021 - Ria Nudrotun Nufus; Muninghar Muninghar (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to analyze and test the Effect of Net Profit Margin and Total Assets Turnover on Profit Growth. The population in this study are all cement industry sub-sector companies in 2017- 2021, totaling 8 companies. The sampling technique used purposive sampling method, so as to get a sample of 6 companies. Data analysis was performed using multiple linear regression analysis with the help of SPSS version 26. Based on the results of the study, it can be concluded that Net Profit Margin has a significant effect on Profit Growth. Total Assets Turnover has a significant effect on Profit Growth. Thus, simultaneously Net Profit Margin and Total Assets Turnover affect Profit Growth.